Absence of Surface IgD Does Not Impair Naive B Cell Homeostasis or Memory B Cell Formation in IGHD Haploinsufficient Humans - Nechvatalova, Jana; Bartol, Sophinus J W; Chovancova, Zita; Boon, Louis; Vlkova, Marcela; van Zelm, Menno C (The Journal of immunology, 2018)
Surface IgD is coexpressed with IgM on naive mature B cells. Still, the role of surface IgD remains enigmatic even 50 y after its initial discovery. In this study, we examined the in vivo role of surface IgD in human B cell homeostasis and Ab responses in four individuals with heterozygous nonsense mutations in IGHD All IGHD heterozygous individuals had normal numbers of B cells and serum Igs and did not show signs of immunodeficiency or immune dysregulation. IgD+ and IgD- naive mature B cells were present in equal numbers and showed similar immunophenotypes, except for decreased expression of CD79b in the IgD- subset. Furthermore, both IgD+ and IgD- naive mature B cells had normal replication histories and similar capacities to differentiate into plasma cells upon in vitro stimulation, and Ig class-switched memory B cells showed similar levels of somatic hypermutations. Thus, human B cells lacking IgD expression develop normally and generate immunological memory in vivo, suggesting that surface IgD might function more restrictedly in regulating of B cell activation to specific antigenic structures.
Keywords: Lymphocyte Activation; Immunoglobulin M; imunoglobulin D; B-Lymphocyte Subsets; membránové proteiny; Cells, Cultured; Humans; haploinsuficience; Membrane Proteins; Cell Differentiation; aktivace lymfocytů; Homeostasis; Immunoglobulin D; B-Lymphocytes; plazmatické buňky; Plasma Cells; imunologická paměť; přesmyk imunoglobulinových tříd; kultivované buňky; podskupiny B-lymfocytů; B-lymfocyty; Haploinsufficiency; lidé; Immunologic Memory; imunoglobulin M; Immunoglobulin Class Switching; buněčná diferenciace; homeostáza